1998
DOI: 10.1053/bbmt.1998.v4.pm9763110
|View full text |Cite
|
Sign up to set email alerts
|

CD20 is a molecular target for scFvFc:zeta receptor redirected T cells: Implications for cellular immunotherapy of CD20+ malignancy

Abstract: The CD20 molecule was evaluated as a B-cell lymphoma target epitope for T cells expressing a CD20-specific single-chain FvFc-zeta (scFvFc:zeta) chimeric receptor. A cDNA construct consisting of a murine kappa leader sequence, CD20-specific scFv, human immunoglobulin (Ig) G1 hinge-C(H)2-C(H)3, the human CD4 transmembrane, and the intracellular signaling domain of the human CD3 complex's zeta chain was synthesized by polymerase chain reaction splice-overlap extension. The human CD4+ Jurkat cell line was electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 43 publications
1
62
0
Order By: Relevance
“…The protein fusion between ffLuc and the zeocin resistance gene dictates that all zeocin-resistant cells also express the ffLuc reporter gene. Firefly luciferase-positive T cells were propagated ex vivo on a 14-day stimulation cycle with 30 ng/ml OKT3, a 5:1 ratio of irradiated allogeneic PBMC and EBV-transformed lymphoblastoid (LCL) feeder cells, and 25 U/ml rhIL-2 (Chiron) as described previously (24). T cells were cultured in RPMI 1640 (Irvine Scientific) with 10% FCS (HyClone), 25 mM HEPES (Irvine Scientific), 2 mM glutamine (Cambrex), and fresh rhIL-2 was added to cultures every 48 h. All functional assays were performed with T cell effectors between days 10 and 14 from stimulation with OKT3.…”
Section: Cell Lines and Growth Conditionsmentioning
confidence: 99%
“…The protein fusion between ffLuc and the zeocin resistance gene dictates that all zeocin-resistant cells also express the ffLuc reporter gene. Firefly luciferase-positive T cells were propagated ex vivo on a 14-day stimulation cycle with 30 ng/ml OKT3, a 5:1 ratio of irradiated allogeneic PBMC and EBV-transformed lymphoblastoid (LCL) feeder cells, and 25 U/ml rhIL-2 (Chiron) as described previously (24). T cells were cultured in RPMI 1640 (Irvine Scientific) with 10% FCS (HyClone), 25 mM HEPES (Irvine Scientific), 2 mM glutamine (Cambrex), and fresh rhIL-2 was added to cultures every 48 h. All functional assays were performed with T cell effectors between days 10 and 14 from stimulation with OKT3.…”
Section: Cell Lines and Growth Conditionsmentioning
confidence: 99%
“…For hematologic malignancies, CAR technology allows targeting of lineage restricted antigens, such as CD19 42 and CD20 43 that are conserved in the malignant counterpart, by clinical trials have been registered in the USA for infusing T lymphocytes expressing CD19-or CD20-specific CARs in patients with B-cell derived malignancies, 44 and results from many of these studies have recently been reported (Table 2). 5,10,[45][46][47][48][49] When analyzing the results of these trials, it is important to appreciate that few patients have so far been enrolled in each study, and each study cohort is heterogeneous with regards to patient age and type/stage of disease.…”
Section: T Lymphocytes Expressing Cd19-and Cd20-specific Carsmentioning
confidence: 99%
“…In early ex vivo studies, both T cells expressing CAR19 (CART19) and CART20 efficiently lysed a wide panel of tumour cell lines expressing CD19 and CD20 antigens, respectively, as well as B cells freshly isolated from patients with B-cell neoplasms. [50][51][52][53][54][55][56] In animal models, CART19 and CART20 also eradicated systemic cell tumours established in severe combined immunodeficient (SCID) mice that were expressing CD19 or CD20. 51,52 These preclinical experiments have supported the notion that under appropriate conditions, T cells can be therapeutically redirected to eliminate malignant B cells and have justified the translation of these genetically engineered T cells to clinical settings.…”
Section: Cd80 Antigenmentioning
confidence: 99%